Modeling of piezoelectric plates with variables separation for static analysis. (13th April 2016) - Vidal, P; Gallimard, L; Polit, O
Abstract: In this work, the modeling of laminated composite plates with embedded piezoelectric layers is addressed through a variables separation approach. Both the displacement and electric potential fields are approximated as a sum of separated functions of the in-plane coordinates x, y and the transverse coordinate z . This choice yields to a nonlinear problem that can be solved by an iterative process. That consists of solving a 2D and 1D problem successively at each iteration. In the thickness direction, a fourth and second-order expansion in each layer is considered for the displacements and the electric potential, respectively. For the in-plane description, classical eight-node quadrilateral finite element is used. Numerical examples involving several representative laminates are addressed to show the accuracy of the present LayerWise (LW) method. It is shown that it can provide quasi-3D results less costly than classical LW computations. In particular, the estimation of the transverse stresses which is of major importance for damage analysis is very good.